2010
DOI: 10.1016/j.dsr2.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical relationships between ultrafiltered dissolved organic matter and picoplankton activity in the Eastern Mediterranean Sea

Abstract: We targeted the warm, subsurface waters of the Eastern Mediterranean Sea (EMS) to investigate processes that are linked to the chemical composition and cycling of dissolved organic carbon (DOC) in seawater. The apparent respiration of semi-labile DOC accounted for 27 ± 18% of oxygen consumption in EMS mesopelagic and bathypelagic waters; this value is higher than Taken together, this study elucidates key relationships between the chemical composition of DOM and heterotrophic metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 81 publications
(58 reference statements)
6
14
0
Order By: Relevance
“…Also, Meador et al [27] reported similar ranges in the surface layer of the EM and suggested that PA and PB were related to DOC. In the present study, PB and DOC were significantly related (all data, n0145, r00.53, P<0.01), indicating that PB exerts a significant control on DOC cycling.…”
Section: Longitudinal Patterns Of Abundance and Biomassmentioning
confidence: 86%
“…Also, Meador et al [27] reported similar ranges in the surface layer of the EM and suggested that PA and PB were related to DOC. In the present study, PB and DOC were significantly related (all data, n0145, r00.53, P<0.01), indicating that PB exerts a significant control on DOC cycling.…”
Section: Longitudinal Patterns Of Abundance and Biomassmentioning
confidence: 86%
“…The water column of the EMS is well oxygenated. The oxygen minimum found at depths of about 1000 to 2000 m is equivalent to 70-75 % of saturation, while in deeper layers ventilation is enhanced by deep-water formation (Meador et al, 2010;Schlitzer et al, 1991).…”
Section: Oceanographic Settingmentioning
confidence: 99%
“…By contrast, very little information is available on DOC dynamics at the surface in open-seawater [Avril, 2002;Santinelli et al, 2008]. In addition, only a few papers report DOC data combined with microbiological information and these are limited to narrow areas [Yoro et al, 1997;Gasol et al, 1998Sempéré et al, 2002Sempéré et al, , 2003Van Wambeke et al, 2004;La Ferla et al, 2005;Meador et al, 2010].…”
Section: Introductionmentioning
confidence: 99%